2022
DOI: 10.1002/tox.23646
|View full text |Cite
|
Sign up to set email alerts
|

Limonene protects human skin keratinocytes against UVB‐induced photodamage and photoaging by activating the Nrf2‐dependent antioxidant defense system

Abstract: Long term exposure to solar ultraviolet B (UVB) radiation is one of the primary factors of premature skin aging and is referred to as photoaging. Also, mammalian skin exposed to UVB triggers an increase in production of α-melanocyte-stimulating hormone (α-MSH), which is critically involved in the pathogenesis of hyperpigmentary skin diseases. This study investigated the protective effect of limonene on UVBinduced photodamage and photoaging in immortalized human skin keratinocytes (HaCaT) in vitro. Initially, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Regarding isolated compounds, few studies have been conducted using limonene or α-pinene. Limonene was shown to protect keratinocytes against UVB-induced photodamage and photoaging [40]. In addition, this compound is part of the commercial product Garnier Dark Spot Corrector [41], thus reinforcing its skin lightening properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding isolated compounds, few studies have been conducted using limonene or α-pinene. Limonene was shown to protect keratinocytes against UVB-induced photodamage and photoaging [40]. In addition, this compound is part of the commercial product Garnier Dark Spot Corrector [41], thus reinforcing its skin lightening properties.…”
Section: Discussionmentioning
confidence: 99%
“…The reported activity might be attributed to the presence of limonene and α-pinene. Indeed, limonene protects HaCaT cells from H 2 O 2 -induced aging [46] and protects human keratinocytes from UVB-induced photoaging by activating Nrf2-dependent antioxidants [40]. UVA-induced photoaging was also prevented by αpinene through the inhibition of matrix metalloproteinase expression [47].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study also showed that limonene protects skin keratinocytes from the damaging effect of UVB radiation. This protection occurs by activating the Nrf2-dependent antioxidant defense system, which helps the skin cells to defend themselves against oxidative stress and damage caused by UVB exposure [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of UVB is absorbed by the ozone layer but still reaches ground level and is absorbed in sufficient amounts to have a deleterious impact on the skin ( 2 , 3 ). UVA and UVB are reported to induce DNA damage, photoaging, and skin cancer ( 4 , 5 ). However, UVA radiation is much less photochemically active and not strongly absorbed by proteins and nucleic acids, so it is generally less harmful than UVB radiation ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%